Pengaruh Perbedaan Budaya Terhadap Perilaku Komunikasi Mahasiswa - Mesi Nuraeni; M. Izul Fikri Pratama; Risma Ananda (Kampret Journal, 2022)
This research focuses on students of the Faculty of Communication Sciences, Nusatara Islamic University, Bandung on cultural differences in communication behavior. The purpose of this study was to determine how students adapt to the culture of communication behavior. This research method is a qualitative method. This research was conducted at the Nusantara Islamic University campus with Fikom students as informants. Collecting data in this study using interviews and observation. Participants are students of the Faculty of Communication, Islamic University of the Archipelago, Bandung. The results of this study Cultural differences greatly affect a person's behavior in communicating, but these differences should not make us as individuals who feel the most correct because it can cause failure in communicating